Glucose control and autonomic response during acute stress in youth with type 1 diabetes: A pilot study. Issue 5 (7th May 2018) - Guan, Ling; Metzger, Daniel L; Lavoie, Pascal M; Collet, Jean‐Paul
Abstract : Background: Type 1 diabetes (T1D) is a chronic source of metabolic and neuropsychological stress, which may eventually lead to autonomic neuropathy and other complications related to micro‐ and macro‐vasculopathies. We aimed to investigate the relationship between T1D chronic stress and autonomic response to acute stress testing that was expected being affected by chronic stress. Methods: Twenty youths with confirmed diagnosis of T1D were assessed. Chronic stress assessment included hemoglobin A1c (HbA1c) ≥7.5%, psychological stress assessed by perceived stress scale (PSS), hypoglycemic events, and proinflammatory cytokines. The acute stress testing used standardized stress video games. Autonomic response to acute stress was assessed by the amplitude and direction of changes in heart rate variability. Analyses determined correlations between changes in parasympathetic nervous system during stress testing and chronic diabetes stressors. Results: A strong correlation was found between the amplitude of high frequency (HF) changes and HbA1c values ( ρ  = 0.74, P  < .001). Youths with HbA1c ≥7.5% showed a larger amplitude of HF changes during acute stress (49% vs 16%, P  < .001) and a higher PSS score (22.5 vs 19.0, P  = .003), compared to those with HbA1c <7.5%. Additionally, among youths with HbA1c ≥7.5%, those with positive changes in HF had a lower level of IL‐8 than those with negative changes (5.40 vs 7.85 pg/mL, P  = .009). Conclusions: Study findings support the need for better understanding the health effects of stress‐related autonomic dysfunction in youth with T1D.